BAROJA Y PENSOS: ESCRITURA, REACCION Y VALORES FAMILIARES - Gutwirth, Eleazar (Res Publica. Revista de Historia de las Ideas Políticas, 2009)
Focusing on Caro Barojaʼs comment on Joseph Penso de la Vega, «the Academy had other wits of his very lineage and bad taste,» this essay shows both how Pensoʼs contemporaries were better able to sustain an adequate reception of his work and how Caro Barojaʼs judgment is premised on a long anti-Semitic tradition rooted in his own lineage or family genealogy. The condemnatory phrase against Penso is more than poor taste: it is also a proof of secular latent racism.